The Development of a Planning-mathematical Method to Achieve a Fair Population Density Using Population Distribution Methods (Case Study on Al-Najaf governorate) - Fadhaa Marouf M. Al-Chalabi; Atheer Marouf M. Al-Chalabi (Engineering and Technology Journal, 2016)
In this study, planning - mathematical methods (concerning the population distribution) were applied inorder to reachspecific numeric results which help to draw up a plan for a justified distribution of the population, and thus obtain spatially balanced development.Some of these methods are the: "Dynamical Radius", the "Concentration Ratio" and the "Rate of Population Growth" to predict the population distribution (as accomplished fact).Then, develop a mathematical method to achieve the justified population density over time, taking into consideration the natural growth of the population in each stage of distribution.